Pre-transplant Quantitative Determination of NPM1 Mutation Significantly Predicts Outcome of AIlogeneic Hematopoietic Stem Cell Transplantation in Patients with Normal Karyotype AML in Complete Remission - Karas, Michal; Steinerova, Katerina; Lysak, Daniel; Hrabetova, Marcela; Jungova, Alexandra; Sramek, Jiri; Jindra, Pavel; Polivka, Jiri; Holubec, Lubos (Anticancer research, 2016)
BACKGROUND/AIM: Minimal residual disease (MRD) in patients with acute myeloid leukemia (AML) before allogeneic hematopoietic stem cell transplantation (alloHSCT) can influence the results of therapy. With the aim of evaluating the potential role of pre-transplant MRD, we studied the impact of pre-transplant MRD level on the outcome of alloHSCT in patients with AML in complete remission (CR). PATIENTS AND METHODS: From 2/2005 to 9/2014, 60 patients with a median age of 54 years (range=30-66 years) with normal karyotype-AML harboring nucleophosmin 1 (NPM1) mutation [53% Fms-related tyrosine kinase receptor 3 internal tandem duplication (FLT3/ITD)-positive] in first (n=45) or second (n=15) CR underwent myeloablative (n=16) or reduced-intensity (n=44) alloHSCT (27% related, 73% unrelated). The MRD level was determined from bone marrow samples using real-time polymerase chain reaction for detection of NPM1 mutations before starting the conditioning regimen. RESULTS: The estimated probabilities of 3-year relapse, event-free survival (EFS) and overall survival (OS) for the whole cohort were 28%, 54%, and 59%, respectively. Statistical analysis showed that only age over 63 years and high MRD level affected alloHSCT outcome. Pre-transplant MRD level of 10 mutant copies of NPM1 per 10,000 Abelson murine leukemia viral oncogene homolog 1 (ABL) copies had the strongest statistical significance, and detection of higher MRD level (>10 NPM1-mutant copies) before alloHSCT was associated with increased overall mortality (hazard ratio=3.71; 95% confidence interval=1.55-9.06; p=0.004). The estimated probabilities of 3-year relapse, EFS, and OS were 6%, 72%, and 75% for patients with a low level of MRD and 48%, 35%, and 40% for patients with a higher level. CONCLUSION: Our data showed that the pre-transplant level of MRD in patients with normal karyotype AML harboring NPM1 mutation in CR provides important prognostic information, which as an independent prognostic factor predicts transplant results.
Keywords: senioři; jaderné proteiny; Nucleophosmin; Preoperative Period; Nuclear Proteins; Remission Induction; Acute myeloid leukemia; karyotyp; výsledek terapie; Middle Aged; mužské pohlaví; mutace; Leukemia, Myeloid, Acute; Adult; Karyotype; Hematopoietic Stem Cell Transplantation; předoperační období; ženské pohlaví; Mutation; transplantace hematopoetických kmenových buněk; Humans; allogeneic hematopoietic stem cell transplantation; akutní myeloidní leukemie; nukleofosmin; lidé středního věku; minimal residual disease; indukce remise; dospělí; Female; Aged; Treatment Outcome; nucleophosmin 1 mutation; lidé; Male